Blockade of the interaction between Bcr-Abl and PTB1B by small molecule SBF-1 to overcome imatinib-resistance of chronic myeloid leukemia cells. Issue 1 (1st March 2016) - Elgehama, Ahmed; Chen, Wei; Pang, Juan; Mi, Shanwei; Li, Jiahuang; Guo, Wenjie; Wang, Xingqi; Gao, Jian; Yu, Biao; Shen, Yan; Xu, Qiang
Highlights: SBF-1 showed preferential cytotoxicity toward K562 and imatinib-resistant K562/G cells. SBF-1 induced apoptosis by downregulating the PI3K/Akt signaling. SBF-1 enhanced the degradation of Bcr-Abl protein. SBF-1 disrupted the interaction between Bcr-Abl and PTP1B. SBF-1 induced Bcr-Abl degradation through ubiquitination via the lysosomal pathway. Abstract: In this study, a synthetic steroidal glycoside SBF-1 had strong and preferential antitumor effects on the human chronic myeloid leukemia (CML) cell line K562 and its imatinib-resistant form K562/G. SBF-1 induced apoptosis in both cell lines without any effect on cell cycle arrest. It also inhibited the activation of PI3K/Akt pathway members, such as PI3K and Akt, as well as downstream targets mTOR and Bcl-2. Moreover, the degradation of the Bcr-Abl protein was induced by SBF-1 in a concentration- and time-dependent manner. Using a pull-down assay, SBF-1 was found to bind to both Bcr-Abl and PTP1B and disrupted the interaction between them. SBF-1 triggered the degradation of Bcr-Abl through ubiquitination via the lysosome pathway. Taking together these findings, this study, for the first time, suggests that the blockade of the interaction between Bcr-Abl and PTP1B may be a feasible strategy for the treatment of CML, especially CML with resistance to Bcr-Abl kinase inhibitor imatinib. Our study also indicates that SBF-1 may serve as a leading compound for novel anti-CML therapeutic agents.